Imbulan Tatambaan: Revitalisasi Kearifan Lokal Melalui Pelestarian Tumbuhan Herbal Lahan Basah - Muhammad Thoriq Islami; Setia Budhi; Qolbiatul Fitri; Ahyati Kamilazzahra; Cindy Ramadhita Putri; Ahmad Faqih; Milda; Khansa Witha Prayuda (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2023)
Lepasan Village is an area where many medicinal plants grow, this is what makes the people of Lepasan Village especially in the Sei area. Getas has local wisdom regarding the types and benefits of medicinal plants. However, the people of Sei. Getas has not optimized the use of these herbal plants as the main treatment used for medical purposes for all people of various age groups. The aim of this community service is to increase local knowledge and public awareness of the importance of using and preserving herbal plants as a treatment for overcoming health problems. The method used is community empowerment with a process of activating, empowering and empowering which is implemented through activities: identification of herbal plants, focus group discussions on herbal plants, socialization of herbal plants, provision of demonstration plots, learning to cook herbal plants for young people. This community service was carried out from mid-July to the end of August and involved the entire community of Lepasan Village, especially in the Sei Getas area. The results of this service are 1) indications of medicinal plants extracted based on local knowledge of the surrounding community, 2) remembering people's memories regarding herbal plants, 3) making people aware not to forget local wisdom regarding herbal plants. 4) planting as an effort to make it easier for people to find plants with medicinal properties, 5) training the younger generation to be able to process plants with medicinal properties. Revitalizing local community wisdom regarding herbal plants can make people more optimal in utilizing herbal plants. This empowerment makes people more empowered, especially in terms of traditional medicine without having to depend on chemical drugs. Apart from that, this service allows the community to introduce the oldest local wisdom to the younger generation.